(untitled) (Research, Society and Development, 2023)
In Mozambique, despite improvements in literacy and school enrolment rates over the recent decades, the gender disparity in terms of economic opportunity has not improved significantly among the younger cohort of the population. Most of the poor people live in rural areas affected by armed conflicts, where there are higher rates of illiteracy and infant mortality, limited access to energy, safe water and sanitation. In these rural communities, where employment options in the non-agricultural sector are extremely limited, vocational training opportunities for women is essential aspects for boosting job creation and generating new employment opportunities. Institutions of higher education, through university extension, can be driving forces of sustainable local development, based on interrelationship between the University and society and exchange of systematized/academic and popular knowledge. Thus, the aim of this study is to describe challenges and opportunities in conducing intensive training for economic empowering of young underprivileged girls in areas of armed conflict in Mozambique. Methodologically, transferring of knowledge took place by combining methods of course and practical demonstration. The findings of the study suggest that the effectiveness of the university extension process cannot be achieved by following the traditional teaching method, by which knowledge transfer is hierarchical - from teacher to student, but rather, using different teaching and learning methods, according to the needs and profile of the trainees. Also, making the timing and location of classes and training convenient for all women can help to ensure high rates of take-up a more harmonized work–family balance.